Quick diagnostic approach for HIV/STDs among migrants: results from a monocentric Italian cohort - Fiore, Vito; Manca, Valentina; De Vito, Andrea; Colpani, Agnese; Maida, Ivana; Madeddu, Giordano; Babudieri, Sergio (The Journal of Infection in Developing Countries, 2023)
Introduction: Migration has a direct influence on sexual health. Differences both in sexual networks and the risk of sexually transmitted diseases (STDs) between racial or ethnic minorities and the native population have been described in the literature. Methodology: We collected data on medical history, physical examination, and human immunodeficiency virus (HIV)/STDs tests. Screenings were proposed basing on Centers for Disease Control (CDC) 2018 guidelines on STDs. Patients underwent peer-to-peer counselling before screening. Results: We included data of 391 patients (both outpatients and migrants living in facility centers). The median age was 30 (range 24-38) years, and the majority were male (198/391; 50.6%). Among them, 389 (99.4%) were counselled, and 371 (94.8%) accepted the screening. We found 155 (41.7%) HBsAg/Anti-HBc positive tests, 4 (1%) HIV positive screenings, 1 (0.2%) hepatitis C virus (HCV) infection, 47 (12%) genital/perianal warts, 29 (2.3%) cases of syphilis, and 13 (3.3%) molluscum contagiosum. Conclusions: Migrants have high-risk sexual behavior. Despite this, they may have a low perception of risk and healthcare needs. An approach based on quick tests was demonstrated to be useful in increasing the screening acceptance. However, the retainment in care was low, as in previous studies. Access to HIV/STDs screening and treatment should be implemented. The development of specific retainment in care pathways is still needed to reduce the lack of follow-up.